Pengendalian Kimia dan Resistensi Vektor Anopheles Dewasa pada Kawasan Endemis Malaria di Dunia - Musfirah, Musfirah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Various methods of malaria vector control has been done. Insecticides which using repeatedly impact new problems for the emergence of vector resistance. Hence, optimization  about active ingredient  in the insecticide  product  should take notice  to  the development  of  insecticide resistance  mechanisms for  malaria  vectors. Literature review which  assess and discuss  adult Anopheles sp resistance  for  chemical control programme  were  still limited to certain insecticides. The aim  of  this  literature review is  collecting and  findings  evidence has been produced  by researchers which  associated  with  chemical control of  vector  and   variety  of  adult  Anopheles resistance  as  a  strategy  to eradicate malaria endemic cases. Method: This literature review prepared by systematic review methods.Google database is used as the primary source of search with keyword "adult Anopheles", "resistance", insecticide”, and chemical control".  Inclusion  and  exclusion criteria  applied  to  select  journals  that  are  relevant of  this literature review’s topic. Collected 41 articles and 10 articles are matched with inclusion criteria. Results: Chemical control obtain cause Anopheles sp resistance to certain chemical insecticides. The involvement of  Anopheles sp knockdown resistance (kdr) mutations  as  a  genetic factor in the resistance mechanism, bio-ecological factors  and  operational  factors (insecticide  types, application techniques, dose,  frequency, time and  manner  of  application/intervention)  as  the  primary  cause of  chemical  insecticide  resistances. Conclusion: To maintain  this  programme, we needs  government policies are vector  control  integrated  through  research, assessment, and development  of  vector  resistance mechanisms  with  insecticides to achieve the goals  for  globally  malaria’s free in 2020.